2014
DOI: 10.1182/blood.v124.21.370.370
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome in a Large Cohort of Prospectively Treated Adult Patients with T-Lymphoblastic Lymphoma (T-LBL) Despite Slowly Evolving Complete Remission Assessed By Conventional Radiography

Abstract: LBL is a rare subtype of NHL and mostly displays a T-cell phenotype. The WHO classification combines acute lymphoblastic leukemia (ALL) and LBL; pts with ≥ 25% bone marrow (BM) infiltration are considered as ALL. LBL pts are usually treated according to ALL protocols and sometimes reported within ALL trials. There are however specific clinical and management questions, such as role of mediastinal irradiation (MedRad), optimal remission evaluation or risk stratification and there is a lack of prospective trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…This question was addressed with better methodology by two recent studies. In the GMALL trial postinduction, PET results were significantly associated with the response obtained after consolidation I (PET+: 0/21 CRu vs. 10/22 PR [partial remission], P = 0.001), suggesting an equivalence between CR and PET‐negative CRu, which may be informative eliminating the need for intensification of chemotherapy or mediastinal irradiation . In the GRAALL‐Lysa study, PET results did not predict long‐term outcome ; however, end of induction and CT results correlated significantly with PET data.…”
Section: Response Assessment and Risk Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…This question was addressed with better methodology by two recent studies. In the GMALL trial postinduction, PET results were significantly associated with the response obtained after consolidation I (PET+: 0/21 CRu vs. 10/22 PR [partial remission], P = 0.001), suggesting an equivalence between CR and PET‐negative CRu, which may be informative eliminating the need for intensification of chemotherapy or mediastinal irradiation . In the GRAALL‐Lysa study, PET results did not predict long‐term outcome ; however, end of induction and CT results correlated significantly with PET data.…”
Section: Response Assessment and Risk Factorsmentioning
confidence: 95%
“…LBL occurs more commonly in children and male patients, and although T‐ and B‐cell LBL are morphologically indistinguishable, the clinical presentation can suggest a different disease biology. The most frequent sites of involvement observed in adults and children are summarized in Tables and .…”
Section: Clinical Presentation and Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, patients with T‐LBL had better outcomes compared to T‐ALL . The role of SCT in adult T‐ALL remains unclear; with some authors recommending SCT in all patients in CR1 and others restricting SCT to higher‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…92,93,[102][103][104][105] Outcomes appear to be superior in AYAs with the use of pediatric designed treatment protocols, particularly with the current practice of utilizing ALL-type regimens, which has resulted in improved disease-free survival of over 70% in recent studies (Table 1). 106,107 An additional approach for advanced LL in the AYA group has been the use of high-dose therapy and autologous or alloSCT. Bouabdallah et al reported the results of alloSCT (n = 12; 11 underwent the procedure in first complete remission [CR1]) and autologous stem cell transplantation (n = 18; 16 = CR1) in patients aged >14 years with a mean age of 35 with advanced LL.…”
Section: Treatment/managementmentioning
confidence: 99%